MAGIC observations of variable very-high-energy gamma-ray emission from PKS1510-089 during May 2015 outburst - Julian Sitarek; Josefa Becerra González; Vandad Fallah Ramazani; Elina Lindfors; Giovanna Pedaletti; Fabrizio Tavecchio; Monica Vazquez Acosta; Stefan Larsson; Kiran Baliyan; Navpreet Kaur; Sameer; Svetlana Jorstad; et al. (Italy, 2022)
PKS1510-089 is a flat spectrum radio quasar located at a redshift of 0.36. It is one of only a few such sources detected in very-high-energy (VHE, >100 GeV) gamma rays. Though PKS1510-089 is highly variable at GeV energies, until recently no variability has been observed in the VHE band. In 2015 May PKS1510-089 showed a high state in optical and in the GeV range. A VHE gamma-ray flare was detected with MAGIC at that time, showing the first instance of VHE gamma-ray flux variability on the time scale of days in this source. We will present the MAGIC results from this observation, discuss their temporal and spectral properties in the multi-wavelength context and present modelling of such emission in the external Compton scenario.
35th International Cosmic Ray Conference, ICRC 2017